1982
DOI: 10.1007/bf02112353
|View full text |Cite
|
Sign up to set email alerts
|

Separation of valtrate and isovaltrate by means of preparative liquid chromatography

Abstract: In this study valtrate and isovaltrate, two isomeric valepotriates present in various Valeriana species, were separated on a preparative scale with a Waters preparative Liquid Chromatography/500 A system. A rapid separation was achieved with the solvent methylene chloride-n-propanol-acetone (99 + 0.5 + 0.5). Extensive use of the recycle mode of the instrument resulted in a considerable reduction of the amount of solvent used, without affecting the purity and the recovery (greater than 90%) of the separated com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…20,21 The values for the dihedral angles together with the corresponding coupling constants are listed in Table 2. The population-weighted average coupling constant for each H-C-C-H dihedral fragment, also included in Table 2, was calculated using the equation 3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The values for the dihedral angles together with the corresponding coupling constants are listed in Table 2. The population-weighted average coupling constant for each H-C-C-H dihedral fragment, also included in Table 2, was calculated using the equation 3 …”
Section: Resultsmentioning
confidence: 99%
“…1 In fact, it is known that this substance causes suppression of rhythmic contractions and relaxed potassium stimulated contractures in guinea-pig ileum. 3 The structure of 1 was definitively established by Hikino et al 2 and further confirmed by total syntheses from ( )-carvomenthone 4 and (C)-carvomenthone. 5 Since then, there have been several other synthetic constructions of 1 conducted to secure its stereochemistry, which was once a focus of dispute.…”
Section: Introductionmentioning
confidence: 92%
“…8 Phytochemical analysis has shown that this plant contains high concentrations of valepotriates, from which valtrate (1) is perhaps the most important active compound of this group. 9 A recent report demonstrated the hypnotic effect and safety of acute treatment of a standarized hydro alcoholic extract of V. edulis ssp. procera on patients suffering from insomnia.…”
mentioning
confidence: 99%
“…The essential oil of valerian contains over 150 compounds including sesquiterpenes (valerenic acid, valeranone), 13 sesquiterpene derivatives (acetoxyvalerenic acid, 3 β ,4 β -epoxyvalerenic acid, hydroxyvalerenic acid, valerane, valerenal, cryptofauronol), 14,15 bicyclic iridoid esters (valepotriates), 16 decomposition products of valepotriates (baldrinal, homobaldrinal, valtroxal), monoterpenes (bornyl acetate and isovalerate), fl avonoids (6 -methylapigenin, hesperidin), 17 furanofuran lignans, alkaloids (valerianine, actinidine), and free amino acids ( γ -aminobutyric acid, arginine, glutamine, tyrosine). Figure 94.1 displays the chemical structures of the major types of compounds in valerian.…”
Section: Chemical Compositionmentioning
confidence: 99%